2009
DOI: 10.1007/978-0-387-78165-5
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo and Quasi-Monte Carlo Sampling

Abstract: , except for brief excerpts in connection with reviews or scholarly analysis. Use in connection with any form of information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed is forbidden. The use in this publication of trade names, trademarks, service marks, and similar terms, even if they are not identified as such, is not to be taken as an expression of opinion as to whether or not they are subject to proprietary rights.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(17 citation statements)
references
References 326 publications
0
17
0
Order By: Relevance
“…Then, the numerical model needs to be run multiple times to generate results that reflect the uncertainties of the input parameters. For this purpose, there exist two main approaches: Monte Carlo (MC) methods, which draw samples from the probability distributions and Polynomial Chaos (PC) methods, which generate a polynomial representation based on the probability distributions (a surrogate model) ( Lemieux, 2009 ; Xiu, 2010 ). MC methods often require thousands of model runs to yield a reliable estimate of the model uncertainty and are thus not suitable for realistic 3D models.…”
Section: Methodsmentioning
confidence: 99%
“…Then, the numerical model needs to be run multiple times to generate results that reflect the uncertainties of the input parameters. For this purpose, there exist two main approaches: Monte Carlo (MC) methods, which draw samples from the probability distributions and Polynomial Chaos (PC) methods, which generate a polynomial representation based on the probability distributions (a surrogate model) ( Lemieux, 2009 ; Xiu, 2010 ). MC methods often require thousands of model runs to yield a reliable estimate of the model uncertainty and are thus not suitable for realistic 3D models.…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned in the introduction, Sobol' indices may be estimated by direct MC or QMC sampling of the numerical simulator [44,6,40]. Alternatively, a surrogate model (e.g.…”
Section: Sobol' Indicesmentioning
confidence: 99%
“…Among the sensitivity measures used in SA studies, Sobol' indices [49] are particularly popular and powerful, and will be the focus of this paper. In UQ studies, such sensitivity indices are commonly estimated using Monte Carlo (MC) or quasi-Monte Carlo (QMC) sampling methods [44,6,40]. Precisely, the simulator is evaluated over a design of experiments whose elements are obtained from a set of independent realizations of the input random variables in the MC case or from a deterministic sequence of variables approaching such realizations efficiently in the QMC case.…”
mentioning
confidence: 99%
“…The derivation of these results along with some more notation and the connection between our methods and the IS and stratification techniques from Arbenz et al (2018), Glasserman et al (1999), andNeddermeyer (2011) can be found in Section 2. There, we also briefly explain how our conditional sampling step reduces the effective dimension of the problem and therefore makes quasi-Monte Carlo (QMC) particularly attractive in our setting; in QMC, pseudo-random numbers (PRNs) are replaced by more homogeneously distributed quasi-random numbers (see, e.g., see Niederreiter (1978), Lemieux (2009), and Dick and Pillichshammer (2010)).…”
Section: Introductionmentioning
confidence: 99%